Application of Picture and Picture in Increasing Student Learning Activeness in Civic Education Subjects - Septiana Wulandari, Nurul; Wantoro, Jan (UIN Raden Mas Said Surakarta, 2024)
This research is an improvement in the learning methods students use during learning. Aims to increase mastery of civic education competencies by applying the Picture And Picture model. This type of research is called Classroom Action Research (CAR). Data was collected using the test method. This classroom action research has four stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this research show that the Picture and Picture Learning Model positively impacts student learning achievement. This result can be seen from students' increasingly solid understanding of the material the teacher presented. The increase occurred from Cycle I to Cycle II. So it can be concluded that the application of the Picture And Picture Model can improve mastery of civic education class II lesson competencies at SD 3 Muhammadiyah Surakarta